Recent Publications (Quarterly Journal of Economics, 1967)
Recent Publications The Quarterly Journal of Economics, Volume 81, Issue 1, February 1967, Pages 165–168, https://doi.org/10.1093/qje/81.1.165 Published: 01 February 1967